Development of a Natural Oil Blend Formulation to Replace Antibiotics and Growth Promoters in Broiler Chicken Feed - Setiyono, Agus; Andriyanto; Mustika, Aulia Andi; Sutardi, Lina Noviyanti; Babikian , Haig; Jha, Rajeev Kumar; Halalludin, Beni; Davtyan, Tigran; Babikyan, Yusef (International Journal of Poultry Science, 2021)
Background and Objective: There has been continued effort to find an alternative to antibiotic growth promoters (AGPs) to improve broiler chicken performance. Several studies have been conducted on the use of herbal active compound for development of natural oil blend formulation (NOBF). This study aimed to explore the effectiveness of NOBF on the productivity, health and safety of broiler chickens. Materials and Methods: The parameters observed were productivity (feed and water consumption, weight gain, final weight, feed conversion ratio (FCR), mortality and meat proximate test), health (red blood cell features-red blood cell count, hematocrit and hemoglobin; white blood cell features-white blood cell count, white blood cell differentiation into lymphocytes, monocytes, heterophils, eosinophils, basophils and the heterophil/lymphocyte ratio; and Newcastle disease antibody titer), safety, liver function [serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxalate transaminase (SGOT)] and kidney function (urea and creatinine). A total of 320 day-old chickens (DOC) were divided in a complete randomized design into 2 groups: one group was given standard feed without AGP or essential oil (control) and the other group was given feed (without AGP) with NOBF added at a dose of 2 kg t–1 feed, with 160 repetitions and dietary treatments were administered for 30 days. Blood samples were collected at the beginning (H0) and end (H35) of the research. Results: The NOBF significantly improved the final weight by week 4 compared to the control (p<0.05), showed lower mortality and did not influence the physiological function, liver function, or kidney function of broiler chickens. Conclusion: The administration of NOBF at a dose of 2 kg t–1 feed to broiler chickens was proven effective in increasing performance and was safe to use (nontoxic).